Understanding advocacy practice in mental health: a multidimensional scalogram analysis of case records - Morrison, P.; Stomski, N.; Whitely, Martin; Brennan, P. (Routledge, 2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Background: Few studies have examined mental health consumers’ motives for seeking advocacy assistance. Aims: This study aimed to identify factors that influenced mental health consumers’ use of advocacy services. Methods: The analysis was based on 60 case records that were sourced from a community advocacy service. Each record was dichotomously coded across 11 variables to generate a series of categorical data profiles. The data set was then analysed using multidimensional scalogram analysis to reveal key relationships between subsets of variables. Results: The results indicated that mental health consumers commonly reported a sense of fear, which motivated them to contact the advocacy service in the hope that advocates could intervene on their behalf through effective communication with health professionals. Advocates often undertook such intervention either through attending meetings between the consumer and health professionals or contacting health professionals outside of meetings, which was typically successful in terms of achieving mental health consumers’ desired outcome. The resolution of most concerns suggests that they were often legitimate and not the result of a lack of insight or illness symptoms. Conclusion: Health professionals might consider exploring how they respond when consumers or carers raise concerns about the delivery of mental health care.